Investigation of The Effect Of Water-Cement Ratio On The Modulus Of Rupture Of Concrete (International Journal of Engineering and Computer Science, 2018)
This paper presents the experimental results of the investigation of the effects of water-cement ratio on the modulus of rupture of concrete. The variations of the flexural strengths of concrete mixes with varying water-cement ratio within 28 days after curing and casting, were experimentally investigated. In all a total of 15 prototype concrete beams were cast (2 specimens from each mixture) and tested so as to determine their flexural strength (modulus of rupture). The design strength level attained ranged between 4.50Mpa to 6.30Mpa for water-cement ratio ranging from 0.48 – 0.62. The results obtained showed that the values of modulus of rupture of concrete, increased as the water-cement ratio increased, until an optimum value of 6.30Mpa was attained at a water-cement ratio of 0.58. However, the water-cement ratios above 0.58, was observed to have a very significant reduction effect on the flexural strength of the concrete. Setting time test for the cement paste used for the concrete, was carried out, alongside the grain size distribution analysis of the aggregates. The initial setting time was 60 mins (1 hr.) while the final setting time was 535 mins (approximately 9 hrs). Grain size distribution of aggregates shows that the sharp river sand is a medium-fine aggregate while the granite chipping is a medium coarse aggregate.